The total chemical synthesis of the monoglycosylated GM2 ganglioside activator using a novel cysteine surrogate1. Issue 49 (21st June 2015) - Sato, Kohei; Kitakaze, Keisuke; Nakamura, Takahiro; Naruse, Naoto; Aihara, Keisuke; Shigenaga, Akira; Inokuma, Tsubasa; Tsuji, Daisuke; Itoh, Kohji; Otaka, Akira
<x xml:space="preserve">Abstract</x> We describe a novel peptide ligation/desulfurization strategy using a β-mercapto-N-glycosylated asparagine derivative. The strategy is successfully applied to the total chemical synthesis of GM2 ganglioside activator protein.